Pseudomonads from wild free-living sea turtles in Príncipe Island, Gulf of Guinea. (October 2017) - Oliveira, Manuela; Serrano, Isa; Santos, José Pedro; Bilocq, Florence; Pereira, Nuno; de Santos Loureiro, Nuno; Tavares, Luis; Pirnay, Jean-Paul; De Vos, Daniel
Highlights: Wild sea turtles from Príncipe Island do not carry antibiotic resistant pseudomonads. Evaluation of resistant bacteria in turtles can contribute to management programs. Resistant bacteria may represent a risk, especially for local human populations. Abstract: Dissemination of antibiotic resistance is a major concern, especially in aquatic environments, where pollution contributes for resistant bacteria selection. These strains may have serious health implications, especially for endangered species, including the sea turtles' hawksbill Eretmochelys imbricata and green turtles Chelonia mydas . We aimed to evaluate the presence of antibiotic resistant pseudomonads in wild sea turtles from Príncipe Island, São Tomé and Príncipe, Guinea Gulf. Isolates were obtained from oral and cloacal swabs of free-living turtles by conventional techniques. Pseudomonads screening was performed by multiplex-PCR ( oprI / oprL ) and biochemical identification and antibiotic resistance profiling were achieved using Vitek2. All pseudomonad isolates were genotyped by Rep-PCR. Thirteen isolates were oprI -positive and classified as pseudomonads, eight from the genus Pseudomonas with the species P. aeruginosa, P. stutzeri, and P. mendocina, and five co-isolated Alcaligenes faecalis . The P. aeruginosa isolate was also oprL- positive. Regarding isolates susceptibility profile, 38.5% were susceptible to all antibiotics tested, and multidrug resistant (MDR) strains were not identified. DNA fingerprinting did not show any specific clonal-cluster similarity. Data on the worldwide incidence of antibiotic resistance among wildlife is still very scarce, especially concerning remote tropical areas. Since Pseudomonas genus has emerged as a group of increasingly reported opportunistic microorganisms in human and veterinary medicine with high resistance levels, it could be used as a tool for environmental resistance surveillance, particularly considering their ubiquity.